2019
DOI: 10.1111/ped.13757
|View full text |Cite
|
Sign up to set email alerts
|

Body knowledge in children with congenital lower limb deficiency

Abstract: Background: In order to effectively improve motor function, a sound understanding of one's bodyfor example, relative spatial position, relationships, names and functions of body partsis essential. The aim of this study was to explore how children with congenital lower limb deficiency (LLD) perceive their bodies, particularly their legs. Methods: Six children with congenital LLD and 14 controls, aged 5-12 years, were recruited for this study. They drew self-portraits and answered questions about names of body p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…16) Furthermore, children with upper limb deficiencies are reportedly also deficient in visuospatial and lexical-semantic body knowledge of the upper limbs. 17) Therefore, to encourage such children to wear, cognise, and use their prostheses as a body part, administering their first prosthesis at an early age is advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…16) Furthermore, children with upper limb deficiencies are reportedly also deficient in visuospatial and lexical-semantic body knowledge of the upper limbs. 17) Therefore, to encourage such children to wear, cognise, and use their prostheses as a body part, administering their first prosthesis at an early age is advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…The participants were asked to draw self-portraits as described previously. 13,14 They were handed a black pencil and a sheet of white paper and were instructed, "Draw a picture of yourself." The portraits were compared between the children with SB and control children in terms of which body parts were drawn.…”
Section: Self-portraits Taskmentioning
confidence: 99%
“…Children with SB showed lower correct response rate for affected body parts (foot) and homologous organ (hand) on the body-part naming task like children with lower or upper limb deficiencies. 13,14 As feet and hands are homologous structures, there may be a cognitive interaction between the comprehension of the lower and upper limbs.…”
Section: Body-part Namingmentioning
confidence: 99%
“…A 2005 review reported greater than 90% of the general population have at least a 1 mm discrepancy in leg length 1 . Numerous factors contribute to LLD, including congenital dysplasia and trauma injuries 2 , 3 . Mechanical imbalance of the lower limbs leads to pelvic tilt and compensatory scoliosis, followed by impaired mobility and hip pain.…”
Section: Introductionmentioning
confidence: 99%